2014
DOI: 10.1016/j.quascirev.2013.09.013
|View full text |Cite
|
Sign up to set email alerts
|

Controls upon the Last Glacial Maximum deglaciation of the northern Uummannaq Ice Stream System, West Greenland

Abstract: Citation for published item:vneD FF nd oertsD hFrF nd eD fFF nd ¡ y gofighD gF nd ieliD eF nd od¡ esD eF @PHIRA 9gontrols upon the vst qlil wximum deglition of the northern ummnnq se trem ystemD est qreenlndF9D uternry siene reviewsFD WP F ppF QPREQRRF Further information on publisher's website: Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
60
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(66 citation statements)
references
References 97 publications
(140 reference statements)
6
60
0
Order By: Relevance
“…Kelly, 1985;Roberts et al, 2009), however, from recent studies (e.g. Corbett et al, 2013;Roberts et al, 2013;Lane et al, 2014;Winsor, 2014;Winsor et al, 2015) it seems likely that most trimlines in Greenland reflect an englacial thermal boundary rather than the LGM ice surface, i.e. that they mark a transition from warm-based ice (below the trimline) to cold-based, non-erosive ice (above the trimline).…”
Section: Last Glacial Maximum Ice Extent and Timing Of Initial Retreatmentioning
confidence: 99%
“…Kelly, 1985;Roberts et al, 2009), however, from recent studies (e.g. Corbett et al, 2013;Roberts et al, 2013;Lane et al, 2014;Winsor, 2014;Winsor et al, 2015) it seems likely that most trimlines in Greenland reflect an englacial thermal boundary rather than the LGM ice surface, i.e. that they mark a transition from warm-based ice (below the trimline) to cold-based, non-erosive ice (above the trimline).…”
Section: Last Glacial Maximum Ice Extent and Timing Of Initial Retreatmentioning
confidence: 99%
“…Sugden [84] classified southern and western Svartenhuk Halvø as displaying little or no glacial erosion, with the north and east classified as landscapes of cirque glaciers and plateau remnants. Recent mapping has reclassified a larger proportion of the peninsula as areas of mountain valley and cirque glaciers [54]. Sedimentological studies in Svartenhuk Halvø reported the presence of deltaic deposits with in situ marine molluscs (thought to be glacioisostatically uplifted), widespread shell-bearing littoral gravel and sublittoral muds, and a single exposure of diamicton [13].…”
Section: Geomorphology and Sedimentologymentioning
confidence: 99%
“…The present ice-free landscape of Greenland is dominated by landscapes resulting from ice sheet activity (e.g. areal scour and selective linear erosion) and those formed through the action of independent valley and mountain glacier systems [54,84]. During full glacial conditions, the majority of land surrounding Greenland was inundated and covered by thick, ice stream and interstream ice as it moved offshore [35].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…e.g. Alley et al, 2005;Bamber et al, 2007;Nick et al, 2009;Ó Cofaigh 10 et al, 2013;Dowdeswell et al, 2014;Lane et al, 2014;Joughin et al, 2014;11 2 Hogan et al, 2016;Sheldon et al, 2016). Jakobshavn Isbrae, in central West and the overall interaction of the glaciers with the marine environment since the…”
Section: Introductionmentioning
confidence: 99%